A possible design and justification for a biogas plant at Nyazura Adventist High School, Rusape, Zimbabwe - Mukumba, Patrick; Makaka, Golden; Mamphweli, Sampson; Misi, Sherpherd (Journal of Energy in Southern Africa, 2013)
The research study was carried out to assess the biogas potential at Nyazura Adventist High School, Rusape, Zimbabwe, a co-educational school with a total enrolment of 700 boarders. The school is connected to the national grid electricity. The electricity is in short supply due to long hours of load shedding. Firewood to be used for heating and cooking purposes is in short supply. The main objective of the study was to make an assessment of biogas potential at the school. The energy demand for the whole school was calculated and it was found to be 2 710 kWh per day. The biogas yields for the feedstocks at the school were estimated. The total biogas yield that could be obtained from the feedstocks was 50 m3 per day. The digesters volume for the feedstocks was estimated and the material requirements for the digesters were also determined. The techno-economic analysis of the proposed project was done. The results suggested that the proposed project was feasible, and it was concluded that the school is capable of producing enough biogas from its feedstocks to support a feasible project. The daily 50 m3 biogas yield is adequate to supply enough electricity for lighting purposes during the load shedding periods.